PERKEMBANGAN BEBERAPA ASPEK PSIKIS ANAK (MORALITAS, EMOSI/PERASAAN, DAN KEAGAMAAN) DAN HUBUNGANNYA DENGAN BELAJAR - Abdul Wahab Syakhrani; Khairunnisa Khairunnisa; Khalimatuz Zahra Tanjung; Maula Muslimah (CV. ADIBA AISHA AMIRA, 2025)
The development of children's psychic aspects plays an important role in influencing their learning process. This study aims to investigate the relationship between the development of children's morality, emotions/feelings, and religion with their learning abilities. Good child morality can shape positive behaviour that supports a conducive learning environment. Healthy emotional development helps children manage stress and anxiety, thus improving concentration and problem-solving abilities. In addition, religious aspects offer ethical and spiritual values that can strengthen internal motivation and the spirit of learning. Through a comprehensive literature analysis of various research and scientific writings, it was found that these three aspects are interrelated and significantly influence children's academic achievement. By understanding this relationship, parents, educators, and education policy makers can design more effective strategies in supporting children's holistic development, thus maximising their learning potential.